Emerging solutions for the dilated native right ventricular outflow tract. (June 2021) - Shahanavaz, Shabana; Tang, Jessica; Gillespie, Matthew J.; Morgan, Gareth J.
Abstract: Transcatheter pulmonary valve replacement in the dysfunctional native right ventricular outflow tract (RVOT) provides an ongoing challenge. Currently available transcatheter pulmonary valves were developed for implantation within surgically placed conduits and bioprosthetic valves, and are often inadequately sized for the dilated native RVOT. The Medtronic Harmony™ (Medtronic, Minneapolis, MN), the Alterra Adaptive Prestent™ (Edwards Life Sciences, Irvine, CA), and the Venus P-valve™ (Venus Medtech, Shanghai, China) are three devices that have been developed in recent years, for the dedicated indication of transcatheter pulmonary valve replacement in the dysfunctional native RVOT. In this article, we describe each of these devices and review the clinical experience with them to date. Highlights: The geometry of the dilated, dysfunctional native RVOT often precludes the use of currently available transcatheter pulmonary valves. The Medtronic Harmony™, the Alterra Adaptive Prestent™, and the Venus P-valve™ are new transcatheter devices for pulmonary valve replacement in the native RVOT. All three devices have thus far demonstrated favorable clinical outcomes, and offer a less invasive alternative to surgical pulmonary valve replacement.